2017
DOI: 10.1371/journal.pone.0187044
|View full text |Cite
|
Sign up to set email alerts
|

Rapid regrowth and detection of microbial contaminants in equine fecal microbiome samples

Abstract: Advances have been made to standardize 16S rRNA gene amplicon based studies for inter-study comparisons, yet there are many opportunities for systematic error that may render these comparisons improper and misleading. The fecal microbiome of horses has been examined previously, however, no universal horse fecal collection method and sample processing procedure has been established. This study was initialized in large part to ensure that samples collected by different individuals from different geographical are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 68 publications
(81 reference statements)
7
21
1
Order By: Relevance
“…Due to that participating horses were located all over Sweden and Norway, and sampling periods were the same for all participants, it was not possible to achieve the exact same number of days between sampling and arrival at laboratory. In a study conducted by Beckers et al 37 , the results showed that equine faecal samples changed in microbial composition rapidly post defecation. Changes included changed diversity and community composition, with increase of several bacterial families including Bacillaceae , Planococcaeae and Enterococcaceae 37 .…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Due to that participating horses were located all over Sweden and Norway, and sampling periods were the same for all participants, it was not possible to achieve the exact same number of days between sampling and arrival at laboratory. In a study conducted by Beckers et al 37 , the results showed that equine faecal samples changed in microbial composition rapidly post defecation. Changes included changed diversity and community composition, with increase of several bacterial families including Bacillaceae , Planococcaeae and Enterococcaceae 37 .…”
Section: Discussionmentioning
confidence: 98%
“…In a study conducted by Beckers et al 37 , the results showed that equine faecal samples changed in microbial composition rapidly post defecation. Changes included changed diversity and community composition, with increase of several bacterial families including Bacillaceae , Planococcaeae and Enterococcaceae 37 . Although the time from sampling to arrival at the laboratory varied in the current study, samples from each matched pair were taken on the same day and sent in the same postal package resulting in no difference in number of days between sampling and analysis between case and control horse samples.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That said, future studies are needed to determine the maximal moisture capacity of the desiccant cartridges and effects of variable moisture content on efficacy. Notably, one study examining the effects of time post-defecation at ambient temperature on the composition of equine feces also detected significant increases in the relative abundance of microbes in the families Bacillaceae and Planococcaceae (as well as Enterococcaceae ), and a trend ( p = 0.055) toward increased abundance of family Moraxellaceae (Beckers et al, 2017). The close agreement of the current room temperature samples with those results (generated in Southern Louisiana) suggests that the changes observed with sub-optimal sample handling of equine feces are relatively conserved across geographical regions, and that the DriBank instrument was capable of abrogating the majority of those changes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis has shown that human rectal swabs stored at room temperature experience characteristic growths of Gammaproteobacteria (Amir et al, 2017). A similar increase in the abundance of proteobacteria was also seen in the microbiota of tadpoles (Nanorana parker) gut samples left thawing at ambient temperature for 12 h (Anslan et al, 2019), while equine feces collected 12 h post-defecation showed sharp increases of families from the Firmicutes phylum (Beckers, Schulz & Childers, 2017). Though the effect of sample storage at ambient temperature has been well-documented across study systems, it has remained unclear whether freezing at −80 C is overly conservative.…”
Section: Introductionmentioning
confidence: 91%